2015
DOI: 10.1007/s11356-015-4827-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of conservative tracer measurement results using the Frechet distribution at planted horizontal subsurface flow constructed wetlands filled with coarse gravel and showing the effect of clogging processes

Abstract: A mathematical process, developed in Maple environment, has been successful in decreasing the error of measurement results and in the precise calculation of the moments of corrected tracer functions. It was proved that with this process, the measured tracer results of horizontal subsurface flow constructed wetlands filled with coarse gravel (HSFCW-C) can be fitted more accurately than with the conventionally used distribution functions (Gaussian, Lognormal, Fick (Inverse Gaussian) and Gamma). This statement is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Further details are found in Dittrich and Klincsik (2015a). The mathematical procedure was published in Dittrich and Klincsik (2015a). Dittrich and Klincsik (2015a) demonstrated that the Frechet distribution is the best-fitting function to effluent point measurement results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further details are found in Dittrich and Klincsik (2015a). The mathematical procedure was published in Dittrich and Klincsik (2015a). Dittrich and Klincsik (2015a) demonstrated that the Frechet distribution is the best-fitting function to effluent point measurement results.…”
Section: Methodsmentioning
confidence: 99%
“…The mathematical procedure was published in Dittrich and Klincsik (2015a). Dittrich and Klincsik (2015a) demonstrated that the Frechet distribution is the best-fitting function to effluent point measurement results. The results show that Frechet had the best average R 2 of the effluent measurement point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Martin [25] generalised the TIS model to non-integer n ≥ 1 to fine-tune the resulting RTD. This generalisation has been used as a stand-alone model and as a building block in reactor networks [13,24,[26][27][28]. Toson et al [29] used the model with a narrow parameter range 0.5 < n < 1.1 to fit the RTD of a continuous powder mixer and linked n to the quality of the mixing process.…”
Section: Introductionmentioning
confidence: 99%
“…The First Order Kinetic Model (FOKM) is the most utilized model for describing the process (Kadlec & Wallace, 2008), however it has not shown good fit to the experimental data because the reactors do not presented an ideal hydraulic behaviour, due to the occurrence of flow anomalies such as dispersion, shortcircuits and the presence of dead zones (Dittrich & Klincsik, 2015), and due to the decay coefficient of organic material suspended in wastewater which varies with the hydraulic retention time (HRT) (Shepherd, Tchobanoglous, & Grismer, 2001). According to Langergraber et al (2009), the simplified assumption of an ideal plug-flow in HSSF-CWs may introduce significant errors to the parameters, as well as the HRT, and consequently on the pollutant removal estimates.…”
Section: Introductionmentioning
confidence: 99%